DEVELOPING TEACHERS’ PEDAGOGICAL COMPETENCE GUIDANCE MODEL FOR TEACHERS OF PRIMARY SCHOOLS IN WEST SUB-DISTRICT OF SEMARANG - Purwanti, Eko; Rukmini, Dwi (The Journal of Educational Development, 2013)
The purposes of the study on which this article is based are: to explain the condition pedagogical competence of primary school teachers in west Semarang subdistrict; to formulate the guidance model for evaluating the teacher pedagogical competence; and find out the effectiveness of the concerned model’s implementation. The method used to develop the modified model of the ones suggested by Borg and Gall (1983) which consists of three main steps: a preliminary study, the process of its development and its finalization. The research results show that the pedagogical competence model of primary school teachers in west semarang subdistrict is still considerable. The implementation of guidance model is done through workshop, colloquium, and direct implementation on the site. The conclusion of this research is that the model can be as an alternative guidance for finding out the teachers’ pedagogical competence. The advantages of the developed model is the fulfillment of the needs to have the guidance to diagnose the concerned teachers’ pedagogical competence dimensions and motivation is achieved. The product implementation can be also used to obtain the monitoring and evaluation information of the pedagogical competence of the teachers. It can furthermore be used as consideration to design the material for the trainers of a teacher training center since it can provide the real needs of pedagogical competence of the teachers going to be trained